2023
DOI: 10.3390/su151410848
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Impacts of Protected Areas, Their Influence on Local Public Support and Their Distribution across Social Groups: Evidence from the Eifel National Park, Germany, during the COVID-19 Pandemic

James McGinlay,
Jens Holtvoeth,
Alfie Begley
et al.

Abstract: Protected Areas are a cornerstone of biodiversity conservation policies, providing significant benefits both for nature and people. This study investigates the diversity, extent, and social and spatial distribution of the social outcomes of the Eifel National Park in Germany and how these are linked with the level of public support for the park, as well as the effect of COVID-19 on these social impacts. Structured questionnaires were distributed to local residents living inside or near the national park. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…A growing body of literature suggests that parks can provide recreational, social, and health benefits to communities and are imperative to urban dwellers [1][2][3][4][5][6]. However, the global coronavirus disease 2019 (COVID-19) pandemic had drastically compromised the accessibility and operational capacity of urban parks [7][8][9]. It greatly jeopardized physical activities and social interactions across countries [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that parks can provide recreational, social, and health benefits to communities and are imperative to urban dwellers [1][2][3][4][5][6]. However, the global coronavirus disease 2019 (COVID-19) pandemic had drastically compromised the accessibility and operational capacity of urban parks [7][8][9]. It greatly jeopardized physical activities and social interactions across countries [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the challenges raised are related to diverse uses of PCAs and the various stakeholder needs that must be balanced in contemporary PCA management. McGinlay and colleagues [19] emphasized the need to recognize and adjust management to offset trade-offs between increased tourism and the well-being of local residents, while Rusvai and colleagues [20] demonstrated that assisted hunting and conservation goals need to be jointly managed. Maretti and colleagues [21] also emphasize the importance of the social context and governance issues and promote enhanced collaborative conservation.…”
mentioning
confidence: 99%